Improving accessibility of IT devices for individuals with disabilities by examining their characteristics and voice of customers - Park, Junghoon (International Journal of Web and Grid Services, 2025)
Accessibility is crucial for individuals with disabilities to participate fully in society. While the USA has implemented systems to ensure accessibility, many countries have more relaxed approaches. Advancements in IT technology have highlighted the importance of IT accessibility, as the expanding range of tasks achievable with these devices may present new challenges for disabled individuals. This paper collects voice of the customer (VoC) data from physically, hearing, or visually impaired people, focusing on the upper limb disabled who are often overlooked and propose guidelines to improve IT device accessibility, including smartphones, tablets, TVs, PCs, and eyemouse. In addition, this paper detailly analyses the characteristics of equipment and devices for three types of physical impairments, investigate VoC, and propose solutions to enhance future IT device accessibility.
Keywords: Accessibility; Customer data; Digital hand; Disability; Disabled individuals; Eyemouse; Impaired people; Physically impaired people; Voice of the customer; Voices of customers; accessibility; digital hands; disability; eyemouse; physically impaired people